Effects of magnetic drift shell splitting on electron diffusion in the radiation belts. Issue 12 (28th December 2016) - Zheng, Liheng; Chan, A. A.; O'Brien, T. P.; Tu, W.; Cunningham, G. S.; Albert, J. M.; Elkington, S. R.
Abstract: Drift shell splitting in the presence of pitch angle scattering breaks all three adiabatic invariants of radiation belt electron motion and produces new diffusion terms that fully populate the diffusion tensor in the Fokker‐Planck equation. The Radbelt Electron Model (REM) solves such a Fokker‐Planck equation and is used to investigate the phase space density sources. Our simulation results and theoretical arguments suggest that drift shell splitting changes the phase space location of the source to smaller L shells, which typically reduces outer zone phase space density enhancements, and this reduction has a limit corresponding to two‐dimensional local diffusion on a curved surface in the phase space. Key Points: Magnetic drift shell splitting in geomagnetic field moves radiation belt electron sources to smaller L shells With typical electron phase space density profiles, drift shell splitting reduces radiation belt electron enhancement The reduction of electron enhancement has a limit corresponding to 2‐D local diffusion on a curved surface in phase space